Inclusive Intervention to Enhance the Fundamental Movement Skills of Children without Hearing: A Preliminary Study. Issue 1 (February 2014) - Gursel, Ferda
The purpose of this study was to assess an intervention program on the fundamental movement skill of students with and without hearing impairment, using the Test of Gross Motor Development–2 (TGMD–2) standardized Turkish norm. Preschool children with and without hearing impairment participated in this study. At the beginning of the study, most of the children with hearing impairment demonstrated developmental delay on the Locomotor subscale (6/7), as did about one-third (4/11) of the children without hearing impairment. For the Object control subscale, 4/7 of children with hearing impairment and none without hearing impairment showed developmental delay prior to the intervention program. After the intervention program, 3/7 children with hearing impairment had developmental delay on the Locomotor subscale. On the Object control subscale, 2/7 children with hearing impairment and none without hearing impairment showed developmental delay. The six-week intervention program improved TGMD–2 scores of children with hearing impairment, yet did not yield statistically significant improvement of fundamental movement skills.